Whole blood dynamic platelet aggregation counting and 1-year clinical outcomes in patients with coronary heart diseases treated with clopidogrel. (3rd October 2021) - Wan, Huaibin; Han, Weichao; Wu, Zhihao; Lie, Zhenbang; Li, Daqiang; Su, Shaohui
Abstract: In the setting of coronary heart diseases (CHDs) on treatment with clopidogrel, ADP-induced platelet aggregation has been demonstrated with ischemic events. However, there were very limited data for predicting ischemic events by platelet function test via dynamic platelet aggregation counting (DPAC). The present study aimed to evaluate the relationship between adenosine diphosphate (ADP)-induced whole blood platelet aggregation rates (PARs) and clinical outcomes in patients with CHDs on treatment with clopidogrel. We have retrospectively analyzed the clinical data of consecutive patients with CHDs based on the electronic medical records between May 2016 and December 2018. The primary endpoint was a composite endpoint events (CEEs) of ischemic cardiovascular events (including acute coronary syndrome, heart failure, transient ischemic attack, and cerebral infarction) and all-cause death. A total of 490 patients (mean age 66.6 years, 71% man) were received ADP-induced PARs via DPAC. On follow-up (mean 374 days), 107 subjects (21.8%) developed CEEs. Cox regression analysis indicated that the risk of CEEs was independently associated with ADP-induced whole blood PARs [HR: 1.023, 95% CI: 1.005–1.041, P = .011]. The distribution of CYP2C19 loss of function gene was higher in patients with on-treatment platelet hyperresponsiveness (10/12 vs 38/75, P = .042). In conclusion, ADP-induced whole blood PARs via DPAC is feasible, which can predict the incidence of 1-year CEEs in patients with CHDs on treatment with clopidogrel. CYP2C19 gene polymorphism was associated with clopidogrel on-treatment platelet hyperresponsiveness.